Spatial patterns of innovation and trade competitiveness - Stefano Breschi; Daniela Palma (European Regional Science Association (ERSA), 1998)
A renewed concern has been growing recently for the role that the spatial organisation of innovation and production plays in determining trade performances. Purely technological externalities can be seen as a core component of this process, and their degree of influence can be investigated in terms of how factors that shape the structure of the innovative activity are definite in space. In the present paper we explore the relationship between technological and trade performances by focusing on the spatial configuration of different structures of the innovative activity in high technology industries in Italy. The data used in the analysis are based on the European Patent Office data base and on trade statistics from the five digit S.I.T.C. classification, and are spatially referenced to the Italy NUT 3 regional partition. Technological and knowledge externalities are modelled through the use of information associated to the connectivity structure of the geographical system under study. The analysis is ultimately aimed at investigating how technology factors evolve with respect to specific and space related carachteristics of the industrial context giving rise to cumulativeness of technology advantages, and to what extent these factors appear to affect trade competitiveness in specific industries. Keywords: spatial externalities. spatial innovation systems. trade competitiveness
Keywords: 330